Talent Management Applications In The Tourism Sector: A Systematic Literature Review Study - Dewi, Emilia Fitriana; Pringgabayu, Dematria (Journal of Tourism, Hospitality and Travel Management, 2026)
The tourism industry is highly vulnerable to shifting global demographics and unprecedented crises, making strategic human resource management and talent retention critical for organizational resilience and competitive advantage. Despite its strategic importance, research on talent management (TM) within this specific sector remains fragmented and lacks a solid theoretical foundation. To address this gap, this study conducts a Systematic Literature Review (SLR) to consolidate empirical evidence on TM applications in the tourism industry and proposes a comprehensive multi-level framework encompassing TM practices, determinants, and results. Guided by the PRISMA framework, 30 peer-reviewed articles sourced from the Scopus database were systematically selected and critically analyzed. The synthesis reveals that current TM research in tourism predominantly focuses on practical, objective methods for advancing talent management systems. Notably, 80% of the reviewed publications focus narrowly on exploring and assessing organizational TM improvements, while only 6 studies integrate crucial strategic elements, such as knowledge management and broader talent development. By highlighting these conceptual blind spots, this review emphasizes the urgent need to transition from traditional HR functions to resilient, knowledge-based talent ecosystems. The proposed framework provides actionable insights for industry practitioners to enhance talent management strategies and outlines a robust agenda for future academic inquiry.